Shoes Names of Their Part and Places (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, the formation of a national complex of folk clothing is influenced by moral and aesthetic ideas, traditions of generations, material and economic living conditions, as well as their relations with other ethnic groups. The peculiarity of this lexicon is that the analysis of its semantics requires constant reference to reality, ethnolinguistic information. The article analyzes the expression of clothing names in ethnolinguistic groups.